Museums and Open-Air Museums in the Implementation of Cultural and Ethnic Tourism in Ukraine - Inna Mylko; Olena Nahornova; Serhii Ozhema (Studia Regionalne i Lokalne)
The article will consider various approaches to defining the essence of cultural and ethnic tourism, and analyse the important aspects of the proposed approaches. The importance of preserving cultural heritage at the level of international organisations is emphasised. The policy of the European Union regarding cultural and ethnic tourism is characterised. The distribution of museums by profile and regions in Ukraine in 2021 is presented. The losses suffered by museums during the military invasion of Russia into Ukraine were assessed. The SWOT analysis was performed to determine the directions of the development of cultural and ethnic tourism of Ukraine in the post-war period. Strategic directions for the development of cultural and ethnic tourism in Ukraine are proposed. Models of state regulation of the sphere of cultural and ethnic tourism are analysed. A set of tools is proposed that will ensure the effectiveness of the functioning of cultural and ethnic tourism. Open-air museums are characterised as a way of preserving tangible and intangible heritage. The distribution of open-air museums by regions of Ukraine has been made. It is proposed that tasks be solved for the full use of open-air museums in the field of cultural and ethnic tourism in Ukraine, taking into account the task of protecting cultural heritage objects from destruction during martial law.